The Warrior-Soldier's Commitment: A Resolute March Toward Christ the King and For His Kingdom - Rakotonindriana David Rolland; Robijaona Rahelivololoniaina Baholy (LingLit Journal Scientific Journal for Linguistics and Literature, 2025)
The warrior's imagery lies at the very heart of Christian spirituality. The peaceful soldier embodies a fruitful tension: a fierce combatant against evil, yet a radical peacemaker toward every individual. This paradox is resolved through the literal demilitarization of the battle. The true enemy is not a human being, but the forces of darkness, sin, and the evil structures that enslave the world. The weapons of this war are divine, not physical, and are expressed through love, justice, and reconciliation. Christ's victory on the Cross, achieved through sacrifice and forgiveness, stands as the supreme model. Agape love thus serves as the primary strategy, capable of disarming the aggressor and breaking the cycles of hatred. This metaphor shapes both an identity and a theology. Analysis reveals a hermeneutic of conquest and a victorious eschatology that reinforce community cohesion and legitimize a hierarchical structure. The pastor becomes the commanding officer, and discipline is valued as a spiritual virtue. However, the use of this imagery carries inherent risks: it can engender spiritual anxiety, a Manichaean dualism, and a dangerous tendency toward blind obedience. The greatest combat for the believer is to use the language of war to advance the cause of peace, without ever betraying the core message of Christ. For the metaphor to remain faithful, clear boundaries must never be breached: the enemy is never a person, the weapons are exclusively spiritual, the objective is reconciliation, the model is the crucified and servant Christ. The Christ-soldier must remain a healer and a peacemaker, fighting with vigor against all that dehumanizes without ever becoming inhuman.